Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's solve this step-by-step.
### Step A: Write a system of equations
Given:
1. Two burgers and three orders of fries cost \[tex]$19.75. 2. Five burgers and two orders of fries cost \$[/tex]37.
Let [tex]\( x \)[/tex] be the cost of one burger.
Let [tex]\( y \)[/tex] be the cost of one order of fries.
We can translate the information into a system of linear equations:
1. [tex]\( 2x + 3y = 19.75 \)[/tex]
2. [tex]\( 5x + 2y = 37 \)[/tex]
### Step B: Solve the problem
Now, we need to solve this system of equations to find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex].
#### Step 1: Multiply the equations to align the coefficients
To eliminate one of the variables, we can align the coefficients of either [tex]\( x \)[/tex] or [tex]\( y \)[/tex]. Let's eliminate [tex]\( y \)[/tex].
We'll multiply the first equation by 2 and the second equation by 3 to get the coefficients of [tex]\( y \)[/tex] to match:
[tex]\[ 2(2x + 3y) = 2 \times 19.75 \][/tex]
[tex]\[ 3(5x + 2y) = 3 \times 37 \][/tex]
This gives us:
[tex]\[ 4x + 6y = 39.50 \][/tex]
[tex]\[ 15x + 6y = 111 \][/tex]
#### Step 2: Subtract the equations to eliminate [tex]\( y \)[/tex]
Now subtract the first modified equation from the second modified equation:
[tex]\[ (15x + 6y) - (4x + 6y) = 111 - 39.50 \][/tex]
[tex]\[ 11x = 71.50 \][/tex]
#### Step 3: Solve for [tex]\( x \)[/tex]
[tex]\[ x = \frac{71.50}{11} = 6.50 \][/tex]
So, the cost of one burger is [tex]\( \$6.50 \)[/tex].
#### Step 4: Substitute [tex]\( x \)[/tex] back into one of the original equations to solve for [tex]\( y \)[/tex]
Using the first original equation:
[tex]\[ 2x + 3y = 19.75 \][/tex]
[tex]\[ 2(6.50) + 3y = 19.75 \][/tex]
[tex]\[ 13 + 3y = 19.75 \][/tex]
[tex]\[ 3y = 19.75 - 13 \][/tex]
[tex]\[ 3y = 6.75 \][/tex]
[tex]\[ y = \frac{6.75}{3} = 2.25 \][/tex]
So, the cost of one order of fries is [tex]\( \$2.25 \)[/tex].
### Step C: Solution to the system of equations
The cost of one burger is \[tex]$6.50, and the cost of one order of fries is \$[/tex]2.25.
### Step A: Write a system of equations
Given:
1. Two burgers and three orders of fries cost \[tex]$19.75. 2. Five burgers and two orders of fries cost \$[/tex]37.
Let [tex]\( x \)[/tex] be the cost of one burger.
Let [tex]\( y \)[/tex] be the cost of one order of fries.
We can translate the information into a system of linear equations:
1. [tex]\( 2x + 3y = 19.75 \)[/tex]
2. [tex]\( 5x + 2y = 37 \)[/tex]
### Step B: Solve the problem
Now, we need to solve this system of equations to find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex].
#### Step 1: Multiply the equations to align the coefficients
To eliminate one of the variables, we can align the coefficients of either [tex]\( x \)[/tex] or [tex]\( y \)[/tex]. Let's eliminate [tex]\( y \)[/tex].
We'll multiply the first equation by 2 and the second equation by 3 to get the coefficients of [tex]\( y \)[/tex] to match:
[tex]\[ 2(2x + 3y) = 2 \times 19.75 \][/tex]
[tex]\[ 3(5x + 2y) = 3 \times 37 \][/tex]
This gives us:
[tex]\[ 4x + 6y = 39.50 \][/tex]
[tex]\[ 15x + 6y = 111 \][/tex]
#### Step 2: Subtract the equations to eliminate [tex]\( y \)[/tex]
Now subtract the first modified equation from the second modified equation:
[tex]\[ (15x + 6y) - (4x + 6y) = 111 - 39.50 \][/tex]
[tex]\[ 11x = 71.50 \][/tex]
#### Step 3: Solve for [tex]\( x \)[/tex]
[tex]\[ x = \frac{71.50}{11} = 6.50 \][/tex]
So, the cost of one burger is [tex]\( \$6.50 \)[/tex].
#### Step 4: Substitute [tex]\( x \)[/tex] back into one of the original equations to solve for [tex]\( y \)[/tex]
Using the first original equation:
[tex]\[ 2x + 3y = 19.75 \][/tex]
[tex]\[ 2(6.50) + 3y = 19.75 \][/tex]
[tex]\[ 13 + 3y = 19.75 \][/tex]
[tex]\[ 3y = 19.75 - 13 \][/tex]
[tex]\[ 3y = 6.75 \][/tex]
[tex]\[ y = \frac{6.75}{3} = 2.25 \][/tex]
So, the cost of one order of fries is [tex]\( \$2.25 \)[/tex].
### Step C: Solution to the system of equations
The cost of one burger is \[tex]$6.50, and the cost of one order of fries is \$[/tex]2.25.
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.